CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY OF THE BASAL PART OF VIGLA SHALE MEMBER (IONIAN ZONE) IN ITHAKI ISLAND; PRELIMINARY RESULTS - Triantaphyllou, M. V.; Karakitsios, V.; Mantzouka, D. (Bulletin of the Geological Society of Greece, 2006)
The calcareous nannofossil biostratigraphy, performed at the basal part of the Vigla Shale Member (Frygano section, Ithakl Island), permits its biostratigraphic correlation with the uppermost part of BC21 biozone (Bown et al., 1998) and the upper part of NC7 biozone (Roth, 1978), which chronostratigraphically point to Late Aptian. This result reinforces the hypothesis that the deposition of Vigla Shales is isochronous in the Ionian zone.